Exploring Brazilin as a Potential Breast Cancer Therapy via Molecular Dynamics Simulation Targeting ERα, 17β-HSD1, and NUDT5 Receptors - Baroroh, Umi; Dasilva, Jasmine Aulia; Sundalian, Melvia; Astriany, Dewi; Ansori, Arif Nur Muhammad; Yee, Jonie C. (Jurnal Kimia Valensi, 2025)
Breast cancer remains one of the leading causes of cancer-related mortality worldwide, suggesting the need for novel therapeutic agents with greater efficacy and fewer side effects. Brazilin, a natural flavonoid compound isolated from Caesalpinia sappan L., has shown promising anticancer activity, particularly against breast cancer cells. This study explores the therapeutic potential of brazilin by evaluating its interactions with three key molecular targets: estrogen receptor alpha (ERα), 17β-hydroxysteroid dehydrogenase 1 (17β-HSD1), and Nudix hydrolase 5 (NUDT5). Using molecular dynamics (MD) simulations, the study assesses the stability and binding interactions of complex systems. The results indicate that brazilin forms a stable complex with ERα, demonstrated by a low RMSD (2.6 Å) and strong hydrogen bonding with Glu353, occupancies of 97.8%, and minimal flexibility at the binding site (average RMSF < 2.5 Å). The binding free energy (ΔG Total) for the ERα–brazilin complex was -54.28 kcal/mol, indicating a stronger affinity than the reference ligand 4-hydroxytamoxifen. Brazilin also showed favorable binding with 17β-HSD1 and NUDT5, with binding energies of -39.71 kcal/mol and -23.23 kcal/mol, respectively. These findings suggest that brazilin may modulate critical targets involved in breast cancer progression, particularly in hormone receptor-positive subtypes. Further experimental validation is necessary to confirm its efficacy and optimize its therapeutic potential.